The Effect of Work Motivation, Leadership, and Organizational Culture on the Performance of Employees at the Bapenda of Lampung Province - Gatronado Garaika; Abdul Halik; Siti Mujanah (Sean Institute, 2025)
The future progress of the Indonesian nation depends heavily on the quality of its human resources, characterized by physical and spiritual well-being, as well as talent and work skills. The primary emphasis in national development efforts is on human resource development. This study aims to determine the influence of work motivation, leadership, and organizational culture on employee performance at the BAPENDA Lampung Province. The sample size for this study was 65 employees. The sampling technique was purposive sampling. This study used a questionnaire to collect data. The data analysis method used was multiple linear regression. The results of this study revealed an influence between work motivation and organizational culture on employee performance, but no influence between leadership and employee performance.